Design of permanent rectification for flare stack structure by using finite element method - Yob, Mohd Shukri; Hussin, A; Tahir, Noor Ayuma; Kurdi, O; Izahar, M.M. (2023)
A flare device is built in a refinery or petrochemical plant to ensure the safety and effective disposal of emitted gases or liquids. A flare is expected to operate for 24h and must be in service for several years without a need to shut it down and is always available for flaring whenever a plant disruption occurs. A proper operating flare system is a vital component to deter a plant disturbance from developing into a disaster. When the flare is exposed to the environment, it can lead the flare to corrosion. It can affect the strength of the flare and needs to maintain the flare by changing the corroded part to a new part. The purpose of this study is to evaluate the stress of flare reinforced by proposed designs I-beam using finite element analysis (FEA). The proposed design was analysed by using FEA at three different boundary conditions focusing on no external disturbance, wind disturbance, and earthquake disturbance. Then, the analysis was validated and compared with experimental analysis conducted on simplified flare design model. The finding shows that the safety factor for the proposed design increases at the welding stress and decreases at the flare (at all three conditions). However, the safety factor still lies in the safe and acceptable condition.